THE ISSUE OF GENDER INEQUALITY IN THE INFORMATION TECHNOLOGY AREA - Santos, Leidjane; Gibertoni, Daniela (Revista Interface Tecnológica, 2023)
With the changes in the labor market, new social problems such as inclusion and gender diversity arise. This work aims to identify the causes that contribute to the number of women in the technology area being lower when compared to the number of men, to present the challenges faced by them and to demonstrate projects that contribute to arouse their interest. by the area. To achieve these objectives, the study methodology was based on a bibliographical review and qualitative research, where a questionnaire was applied through the social networks WhatsApp and Instagram. It can be concluded that the reported problem is a decades-old social construction that generates several difficulties for the studied public, but despite the fact that the number of women is still lower in the area, this difference has been gradually decreasing over the years.